Imperial shipyard (tersane-i amire) in the ottoman empire in 17th century: management and accounting - Toraman, Cengiz; Güvemli, Batuhan; Bayramoglu, Fatih (De Computis, Revista Española de Historia de la Contabilidad., 2010)
The institutions of the Ottoman Empire were under state control. The Imperial Shipyard (Tersane-i Amire) was amongst them. The Imperial Shipyard was established at the end of the 15th century in the Golden Horn (Haliç) - Istanbul and today it continues to operate. This study examines the management and the accounting infrastructure of the shipyard in order to understand the reasons for the mutual interaction between the management and accounting practices of the Ottoman Empire. Thus, this study provides a framework for the state accounting practices of the Ottoman Empire by examining an accounting document regarding the Imperial Shipyard in the year 1661 A.D. (Hegira 1071-1072). Evaluation of the documents indicates that accounting has the ability to meet the needs of the sector which it services. But the concept of cost is not developed within the regarding era.